[Airport taxis ; PBA rookies ; Raiding the DFA [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Focuses on airport taxis that charge a special rate for ferrying incoming passengers at the Manila International Airport; new recruits to the Professional Basketball teams in the Philippines; follow-up story on the consular section of the DFA where there have been accusations of passports for sale.